2018
DOI: 10.1053/j.gastro.2018.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis-Induced Depletion of Syntaxin 2 Promotes Autophagy and Increases Basolateral Exocytosis

Abstract: In studies of human pancreatic tissues and pancreata from STX2-KO and control mice, we found STX2 to block STX3- and STX4-mediated fusion of zymogen granules with the plasma membrane and exocytosis and prevent binding of ATG16L1 to clathrin, which contributes to induction of autophagy. Exposure of pancreatic tissues to CCK-8 or ethanol depletes acinar cells of STX2, increasing basolateral exocytosis and promoting autophagy induction, leading to activation of trypsinogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 55 publications
(129 reference statements)
2
56
0
Order By: Relevance
“…In the gut, in addition to Paneth cells, stromal cells such as intestinal subepithelial myofibroblasts (ISEMFs) are postulated to be important components of the niche, but their precise role and the requirement for mesenchymal cells for normal stem cell function are still being elucidated (1,9,11,22). To begin to understand the role of myofibroblasts in the stem cell niche, we have focused on examining the function of epimorphin (Epim, also known as syntaxin 2), a member of the syntaxin family of membranebound intracellular secretory vesicle docking proteins expressed in ISEMFS that play an important role in regulating cell secretion (4,7,20,21,23,25). We have previously shown that Epim Ϫ/Ϫ mice (with global Epim deletion) have increased small bowel crypt cell proliferation and crypt fission during weaning, resulting in increased small bowel length (23).…”
Section: Introductionmentioning
confidence: 99%
“…In the gut, in addition to Paneth cells, stromal cells such as intestinal subepithelial myofibroblasts (ISEMFs) are postulated to be important components of the niche, but their precise role and the requirement for mesenchymal cells for normal stem cell function are still being elucidated (1,9,11,22). To begin to understand the role of myofibroblasts in the stem cell niche, we have focused on examining the function of epimorphin (Epim, also known as syntaxin 2), a member of the syntaxin family of membranebound intracellular secretory vesicle docking proteins expressed in ISEMFS that play an important role in regulating cell secretion (4,7,20,21,23,25). We have previously shown that Epim Ϫ/Ϫ mice (with global Epim deletion) have increased small bowel crypt cell proliferation and crypt fission during weaning, resulting in increased small bowel length (23).…”
Section: Introductionmentioning
confidence: 99%
“…Here, firstly, our data demonstrated that the hindered autophagy flux was generated upon cerulein stimulation of pancreatic acinar AR42J cells, since it has been a controversial issue whether autophagy promotes or protects against the development of acute pancreatitis [18,19,20]. We showed several pieces of evidence that supported the above temporary Other than this, the measurement of neomycin phosphotransferase (GFP-NeoR) fusion protein [12], another substrate of autophagy, was also found to be significantly increased, reconfirmed the presence of hindered autophagy-the turnover blockage of autophagy in the above setting.…”
Section: Discussionmentioning
confidence: 77%
“…We thank Drs Ding and Wang and the editors for raising these points and allowing us to clarify some of our data and views on the issues raised with regard to our recent article. 1 We first address the first issue, which is the title of this letter-whether autophagy promotes or protects against pancreatitis. We are in agreement that autophagy per se does protect the exocrine pancreas, but this protection is violated and becomes a mechanism of cell injury when the autophagy traffic is perturbed at multiple points by the various triggers of pancreatitis.…”
mentioning
confidence: 99%
“…Of note, pancreatic injury caused by alcohol and experimental supramaximal agonist (CCK or acetylcholine) stimulation, both models of pancreatitis used in our article, also hit more distal steps of the autophagy traffic, at the levels of lysosome (ie, decreasing LAMP2 levels) and autolysosome maturation that leads to defective autolysosome clearance. [1][2][3][4] The latter would then result in impaired cathepsin processing that accounts for excessive and premature trypsinogen activation [2][3][4] and its subsequent leakage into the cytosol inflicting the cell injury. 5 The increased autophagy induction by the mitochondria injury and also endoplasmic reticulum stress pathways by these pancreatitis triggers thus greatly increase trafficking into these distorted distal autophagic steps.…”
mentioning
confidence: 99%
See 1 more Smart Citation